Sejarah Pendidikan Islam: Pertumbuhan dan Pembinaan pada Awal Islam - Hazyimara, Karunia; Syamsuddin; Usman (CV Kalimasada Group, 2023)
This study aims to determine the growth and development of Islamic education in the time of the Prophet Saw. This research uses a qualitative approach. In obtaining data as research material, researchers use library data (library research) with documentation methods. Based on the results of research analysis, it can be seen that in the time of the Prophet (peace be upon him) education had grown through his teachings and guidance from Allah Almighty through the intermediary of the angel Gabriel. This research reveals that in historical facts the Prophet (peace be upon him) educated in a surreptitious and overt way, due to unstable environmental conditions. The knowledge conveyed by the Prophet (saw) is based on the Qur'an as a guide book for Muslims.